Psychological Interventions for Healthcare Providers With PTSD in Life-Threatening Pandemic: Systematic Review and Meta-Analysis - Sun, Zeyuan; Yu, Chuan; Zhou, Yue; Liu, Zhenmi (Frontiers in Psychiatry, 2021)
Objective: To evaluate the effect of psychological interventions on healthcare providers (HCP) with post-traumatic stress disorder (PTSD) due to their necessary exposure in life-threatening pandemic. Search Methods: We performed systematic researches on Medline, Embase, Cochrane Central, PsycInfo, Cochrane Central Register of Controlled Trials, Clinicaltrials.gov, ProQuest PTSD Pubs ProQuest Dissertations & Theses Global and other grey databases by January 2021. Randomized controlled trials involving therapeutic interventions for HCP with PTSD were included. The primary outcome was PTSD symptoms severity. Summary standardized mean differences (SMDs) and 95% credible intervals were estimated using Inverse Variance meta-analysis with fixed effects. Risks of bias were assessed using Cochrane methods. Results: Among 773 citations, this review includes 6 studies randomizing 810 participants. A meta-analysis of the effect of interventions compared to placebo showed a significant reduction of PTSD symptom severity: Cognitive Behavioral Therapy-Brief (CBT-B) (M=27.80, 95% CI: 17.12, 38.48), Cognitive Behavioral Therapy-Long (CBT-L) (M=26.50, 95% CI: 15.75, 37.25), Mindfulness-Based Stretching and Deep Breathing Exercise (MBX) (M= 17.2, 95% CI: 6.57, 27.83). CBT-L and CBT-B also showed significant effect on depression severity.